Analisis Performance Sumur X Menggunakan Metode Standing Dari Data Pressure Build Up Testing - Novrianti, Novrianti (Journal of Earth Energy Engineering, 2016)
The number of production wells refers to the performance of the well, which is shown in the graph of inflow performance relationship (IPR). Reservoir characteristics influence on performance of the well, type of welltest and methods that be used in the determination of IPR. By using the IPR curves, maximum flow rate and the optimal flow rate of the well will be known. Pressure Build Up test is used to know performance and a maximum flow rate of the X well. Well test conducted for 15 hours. The well produced at a constant flow rate than close the wellhead. The Pressure data and time data obtained from the well test. The result of Pressure build-up testing analysis among permeability, skin and flow efficiency. After analyzing the Pressure build-up testing permeability obtained 190 mD, skin + 1,68 and 0,83 flow efficiency. Based on the value of flow efficiency Standing method is the most appropriate method is used to analyze the productivity of X well. Standing appropriate method for wells with skin â  0 and flow efficiency â  1. The maximum flow rate of the X well using Standing Method on the 0,83 flow efficiency was 13,91 MMSCFD